Genetic Sequencing of a Bacterial Pneumonia Vaccine Produced in 1916 - Yongli Xiao; Sebastian M. Gygli; Tomoko Y. Steen; Jeffery K. Taubenberger (Vaccines)
Background/Objectives: Bacterial vaccines were first developed and used in the late 1800s to prevent chicken cholera and anthrax. Bacterial pneumonia vaccines were widely used during the 1918 influenza pandemic, despite the influenza A/H1N1 virus not yet being identified. Studies showed that bacterial pathogens, including Haemophilus influenzae, Streptococcus pneumoniae, and Streptococcus pyogenes, contributed significantly to fatal secondary bacterial pneumonias during the pandemic. In this study, we aimed to characterize the microbial composition of two ampules of a mixed bacterial influenza vaccine produced in 1916, which were labeled as containing killed Bacillus influenzae, Pneumococci, and Streptococcus pyogenes. Methods: DNA was extracted from two 1916-era vaccine ampules, and due to low DNA yields, whole genome amplification (WGA) was performed prior to construction of Illumina sequencing libraries. Deep sequencing was conducted, followed by bioinformatic analysis to identify bacterial DNA content. Consensus genomes were assembled for predominant species, and further analyzed for serotype, phylogeny, and antibiotic resistance genes. Results: The amount of recoverable DNA from these century-old vaccine ampules was limited. The sequencing results revealed minimal detectable S. pneumoniae DNA. The first ampule contained predominantly H. influenzae DNA, while the second vial primarily contained Enterococcus faecium DNA, in addition to S. pyogenes DNA. Consensus genomes for H. influenzae, S. pyogenes, and E. faecium were assembled and analyzed for serotype, phylogeny, and antibiotic resistance genes. Conclusions: This study presents the first genomic analysis of century-old bacterial pneumonia vaccine ampules from the 1918 influenza pandemic era. The findings provide a unique historical perspective on early vaccine formulations and highlight the limitations of early vaccine production.